Accounting for revaluation in Malaysia: an association of its practices with stock wealth - Wan Ismail, Wan Adibah; Kamarudin, Khairul Anuar; Mohamed, Arun (Biro Penyelidikan Dan Perundingan, 2003)
This research investigates the relationship between revaluation surplus and stock wealth, as well as the determinants of revaluation practices in Malaysia. The sample comprises 100 companies listed on the Kuala Lumpur Stock Exchange during the period 1998–2001. Results from ordinary least squares (OLS) regression support the alternative hypothesis that revaluation surplus is associated with stock wealth. The findings from logit regression reveal that revaluation practices are associated with higher earnings, larger company size, lower dividends, lower liquidity, and lower risk. This study, conducted in an economically and culturally different context from existing studies, aims to contribute to the current literature on revaluation practices.